BOOK REVIEW: CRITICAL THINKING - DIEORDITSA, Taiana; TOLMACHOV, Volodimir (Physical and Mathematical Education, 2024)
«Critical Thinking» by J. Haber provides an overview of critical thinking’s history, the skills required for it, and current pedagogical efforts to develop it.